Penerapan Metode Diagnosis Cepat Virus Avian Influenza H5N1 dengan Metode Single Step Multiplex RT-PCR - Haryanto, Aris; Ermawati, Ratna; Purwaningrum, Medania; Wahyu Yudianingtyas, Dini; Haryadi Wibowo, Michael; Rangga Tabbu, Charles (Jurnal Veteriner; Vol 11 No 4 (2010), 2010)
Avian influenza (AI) virus is a segmented single stranded (ss) RNA virus with negative polarity andbelong to the Orthomyxoviridae family. Diagnose of AI virus can be performed using conventional methodsbut it has low sensitivity and specificity. The objective of the research was to apply rapid, precise, andaccurate diagnostic method for AI virus and also to determine its type and subtype based on the SingleStep Multiplex Reverse Transcriptase-Polymerase Chain Reaction targeting M, H5, and N1 genes. In thismethod M, H5 and NI genes were simultaneously amplified in one PCR tube. The steps of this researchconsist of collecting viral RNAs from 10 different AI samples originated from Maros Disease InvestigationCenter during 2007. DNA Amplification was conducted by Simplex RT-PCR using M primer set. Then, bysingle step multiplex RT-PCR were conducted simultaneously using M, H5 and N1 primers set. The RTPCRproducts were then separated on 1.5% agarose gel, stained by ethidum bromide and visualized underUV transilluminator. Results showed that 8 of 10 RNA virus samples could be amplified by Simplex RTPCRfor M gene which generating a DNA fragment of 276 bp. Amplification using multiplex RT-PCRmethod showed two of 10 samples were AI positive using multiplex RT-PCR, three DNA fragments weregenerated consisting of 276 bp for M gene, 189 bp for H5 gene, and 131 bp for N1. In this study, rapid andeffective diagnosis method for AI virus can be conducted by using simultaneous Single Step Multiplex RTPCR.By this technique type and subtype of AI virus, can also be determined, especially H5N1.
Keywords: H5N1, Reverse Transcriptase PCR (RT-PCR), Single Step Multiplex RT-PCR, agarose gel electrophoresis.